2004
DOI: 10.1177/0731684404041149
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Micro-Injection Molding Process using Grey Relational Analysis and MoldFlow Analysis

Abstract: Microsystem technology is a compound technology including optic, mechanism, electricity, material, control and chemistry, etc. This technology can miniaturize products and increase their function, quality, trustworthiness and addendum. Micro-injection molding is a branch of the micro-electro mechanical system. The size of the product is in nanometers. It is important to produce the product for micro-injection molding technology today. The research of micro-injection molding is still in the early stages. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 4 publications
(1 reference statement)
0
12
0
Order By: Relevance
“…Several other simulation experiments were also reported in the literature (Yu et al 2004;Shen and Wu 2002;Young 2005;Mehta et al 2003;Shen et al 2004;Majmundar et al 2005;Sammoura et al 2007).…”
Section: Examples Of Simulation Experimentsmentioning
confidence: 73%
“…Several other simulation experiments were also reported in the literature (Yu et al 2004;Shen and Wu 2002;Young 2005;Mehta et al 2003;Shen et al 2004;Majmundar et al 2005;Sammoura et al 2007).…”
Section: Examples Of Simulation Experimentsmentioning
confidence: 73%
“…The volumetric-filling point exhibits a significant abrupt rise in pressure, which can be easily observed by the first derivative of cavity pressure with respect to time. The grey predictor design in this research is based on a GM(1,1) grey model, featured by its light computational burden and common use in grey forecasting [13][14][15].…”
Section: Cavity Pressure Based Grey Prediction Switchover Methodsmentioning
confidence: 99%
“…The findings showed that the product quality has been improved by 20% at the optimal parameter setting. With the similar integration method, [54] performed experiments on four common polymers (PP, PC, PS, and POM), comparing the effects that moulding process parameters had on their degree of warpage formation, pressure distribution, temperature distribution, and fill time of the parts. PS was found to have the smallest temperature difference which causes smaller warpage and shrinkage.…”
Section: Integration Of Taguchi Methods With Grey Relational Analysis mentioning
confidence: 99%